2019
DOI: 10.1101/816603
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The latitudinal gradient in hand-wing-index: global patterns and predictors of wing morphology in birds

Abstract: An organism's ability to disperse influences many fundamental processes in 27 ecology. However, standardised estimates of dispersal ability are rarely available, and thus 28 the patterns and drivers of broad-scale variation in dispersal ability remain unclear. Here we 29 present a global dataset of avian hand-wing index (HWI), an estimate of wingtip pointedness 30 widely adopted as a proxy for flight efficiency and dispersal in birds. We show that HWI is 31 correlated with geography and ecology across 10,391 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
1
5
0
Order By: Relevance
“…of closed versus open-area species (Sheard et al, 2019), analysis of our categorization of species into forest or non-forest suggests that forest species are indeed poorer dispersers (Figure S1) and that this therefore may be a viable alternative hypothesis as to why the proportion of forest species varies with latitude.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…of closed versus open-area species (Sheard et al, 2019), analysis of our categorization of species into forest or non-forest suggests that forest species are indeed poorer dispersers (Figure S1) and that this therefore may be a viable alternative hypothesis as to why the proportion of forest species varies with latitude.…”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis postulates that species richness decreases with latitude because species require greater dispersal ability to move from the equatorial refugia of the last glacial maxima to the relatively new habitat of the high latitudes (Brown, 2014;Jablonski et al, 2006). This hypothesis is supported for the LBG in birds by the latitudinal gradient in hand wing index; a widely used proxy for dispersal ability (Sheard et al, 2019, Weeks et al, 2023, and could explain our observed latitudinal pattern in the proportion of forest species, if forest species are generally poorer dispersers than generalist or open area species. Whilst a recent analysis found no significant differences in the hand wing index…”
Section: Discussionmentioning
confidence: 98%
“…More complex traits to survive in high-energy environments might be associated with the increased biotic interactions in these environments, such as competitive and pathogenic interactions (Schemske et al 2009; Díaz et al 2013). Data sets of whole genomes and detailed physiology across bird taxa (e.g., Jarvis et al 2014; Sheard et al 2019), will bring a more complete picture of the impact of metabolism and the environment on avian whole-genome evolution.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore suggest that while wingtip shape indices can be valuable proxies in broad views of ecomorphological relationships (e.g. 30,31 ), they provide too coarse of a morphological measurement to be useful in taxonomically-broad studies of flight biomechanics.…”
Section: Additional Considerationsmentioning
confidence: 99%
“…The geometry of a wing influences how it interacts with the air, and thus the lift and drag forces that it generates 22 . Consequently, wing shape in birds is related to flight and migration behavior [23][24][25][26][27][28] and numerous other aspects of avian biology [29][30][31][32][33] . Much work has been done describing how planform wing shape (2-dimensional shape in the wing span vs. chord dimensions) is related to avian aerodynamics [34][35][36][37][38][39] .…”
mentioning
confidence: 99%